Efficacy EMS and DES on Mutagenesis and seedling characters of Eleusine coracana L. Gaertn. - K. Aviya, L. Mullainathan (Journal of Ecobiotechnology, 2018)
This study was performed by exposing the seeds of Finger millet (Eleusine coracana L. Gaertn.) Var CO -13 to Ethyl Methane Sulphonate (EMS) and Diethyl sulphate (DES). The observations were made on seed germination and survivability in M1 generation. The study revealed that germination percentage and survivability were decreased by increasing concentration of the mutagens when compared to the control. The LD50 value was found in 30mM of EMS and 40mM of DES. So it was found that both mutagens at lower treatments have influenced less biological damage and could be suitable for inducing desirable mutations in Finger millet.